Web-Based Cognitive Behavioral Therapy for Female Patients With Eating Disorders: Randomized Controlled Trial - ter Huurne, Elke D; de Haan, Hein A; Postel, Marloes G; van der Palen, Job; VanDerNagel, Joanne EL; DeJong, Cornelis AJ (JMIR Publications, 2015)
BackgroundMany patients with eating disorders do not receive help for their symptoms, even though these disorders have severe morbidity. The Internet may offer alternative low-threshold treatment interventions. ObjectiveThis study evaluated the effects of a Web-based cognitive behavioral therapy (CBT) intervention using intensive asynchronous therapeutic support to improve eating disorder psychopathology, and to reduce body dissatisfaction and related health problems among patients with eating disorders. MethodsA two-arm open randomized controlled trial comparing a Web-based CBT intervention to a waiting list control condition (WL) was carried out among female patients with bulimia nervosa (BN), binge eating disorder (BED), and eating disorders not otherwise specified (EDNOS). The eating disorder diagnosis was in accordance with the Diagnostic and Statistical Manual of Mental Disorders, 4th edition, and was established based on participants' self-report. Participants were recruited from an open-access website, and the intervention consisted of a structured two-part program within a secure Web-based application. The aim of the first part was to analyze participant's eating attitudes and behaviors, while the second part focused on behavioral change. Participants had asynchronous contact with a personal therapist twice a week, solely via the Internet. Self-report measures of eating disorder psychopathology (primary outcome), body dissatisfaction, physical health, mental health, self-esteem, quality of life, and social functioning were completed at baseline and posttest. ResultsA total of 214 participants were randomized to either the Web-based CBT group (n=108) or to the WL group (n=106) stratified by type of eating disorder (BN: n=44; BED: n=85; EDNOS: n=85). Study attrition was low with 94% of the participants completing the posttest assignment. Overall, Web-based CBT showed a significant improvement over time for eating disorder psychopathology (F97=63.07, P<.001, d=.82) and all secondary outcome measures (effect sizes between d=.34 to d=.49), except for Body Mass Index. WL participants also improved on most outcomes; however, effects were smaller in this group with significant between-group effects for eating disorder psychopathology (F201=9.42, P=.002, d=.44), body dissatisfaction (F201=13.16, P<.001, d=.42), physical health (F200=12.55, P<.001, d=.28), mental health (F203=4.88, P=.028, d=.24), self-esteem (F202=5.06, P=.026, d=.20), and social functioning (F205=7.93, P=.005, d=.29). Analyses for the individual subgroups BN, BED, and EDNOS showed that eating disorder psychopathology improved significantly over time among Web-based CBT participants in all three subgroups; however, the between-group effect was significant only for participants with BED (F78=4.25, P=.043, d=.61). ConclusionsWeb-based CBT proved to be effective in improving eating disorder psychopathology and related health among female patients with eating disorders. Trial RegistrationNederlands Trial Register (NTR): NTR2415; http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=2415 (Archived by WebCite at http://www.webcitation.org/6T2io3DnJ).